CAR T-cell therapy for systemic lupus erythematosus: current status and future perspectives - Zhou, Jincai; Lei, Bixia; Shi, Feifei; Luo, Xinran; Wu, Kai; Xu, Yanhong; Zhang, Yuting; Liu, Rongjiao; Wang, Huajing; Zhou, Joy; He, Xiaowen (Frontiers in Immunology, 2024)
Systemic lupus erythematosus (SLE) and lupus nephritis (LN) are debilitating autoimmune disorders characterized by pathological autoantibodies production and immune dysfunction, causing chronic inflammation and multi-organ damage. Despite current treatments with antimalarial drugs, glucocorticoids, immunosuppressants, and monoclonal antibodies, a definitive cure remains elusive, highlighting an urgent need for novel therapeutic strategies. Recent studies indicate that chimeric antigen receptor T-cell (CAR-T) therapy has shown promising results in treating B-cell malignancies and may offer a significant breakthrough for non-malignant conditions like SLE. In this paper, we aim to provide an in-depth analysis of the advancements in CAR-T therapy for SLE, focusing on its potential to revolutionize treatment for this complex disease. We explore the fundamental mechanisms of CAR-T cell action, the rationale for its application in SLE, and the immunological underpinnings of the disease. We also summarize clinical data on the safety and efficacy of anti-CD19 and anti-B cell maturation antigen (BCMA) CAR-T cells in targeting B-cells in SLE. We discuss the clinical implications of these findings and the potential for CAR-T therapy to improve outcomes in severe or refractory SLE cases. The integration of CAR-T therapy into the SLE treatment paradigm presents a new horizon in autoimmunity research and clinical practice. This review underscores the need for continued exploration and optimization of CAR-T strategies to address the unmet needs of SLE patients.